2015
DOI: 10.1097/nmd.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole Adjunct Treatment in Bipolar I or II Disorder, Depressed State

Abstract: The symptomatic course of bipolar disorder (BPD) is chronic and dominated by depression. As recurrence rates are high, maintenance therapy is required. Although efficacious, mood stabilizers may be hampered by poor adherence, and second-generation antipsychotic medications may be associated with weight gain and metabolic abnormalities. There is evidence to suggest that aripiprazole is beneficial in major depressive disorder and BPD with depression. We therefore investigated 2-year clinical outcomes with aripip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The second study used the Self‐reported Medical Outcomes Study SF‐36 Psychosocial Function and Health‐rating Questionnaire to assess improvements in physical, social, and major role activities due to poor health and the association with symptomatic remission and clinical recovery in acutely manic patients with BP‐I receiving daily olanzapine monotherapy in the 49‐week open‐label extension of a 3‐week randomized controlled trial. The third and most recent study used the Sheehan Disability Scale to assess functional recovery in family, social and work/school domains over 2 years in patients with BP‐I or BP‐II openly treated with aripiprazole and an adjunct mood stabilizer.…”
Section: Resultsmentioning
confidence: 99%
“…The second study used the Self‐reported Medical Outcomes Study SF‐36 Psychosocial Function and Health‐rating Questionnaire to assess improvements in physical, social, and major role activities due to poor health and the association with symptomatic remission and clinical recovery in acutely manic patients with BP‐I receiving daily olanzapine monotherapy in the 49‐week open‐label extension of a 3‐week randomized controlled trial. The third and most recent study used the Sheehan Disability Scale to assess functional recovery in family, social and work/school domains over 2 years in patients with BP‐I or BP‐II openly treated with aripiprazole and an adjunct mood stabilizer.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding appetite, McElroy et al showed increased and decreased appetite. A mild weight gain was reported by Malempati et al [ 40 ], while Dunn et al [ 37 ] demonstrated an increase in glucose levels, with concentrations in the normal range. All other trials did not find any weight change during aripiprazole treatment, but, of note, in most studies, the treatment duration was only of some weeks.…”
Section: Resultsmentioning
confidence: 89%
“…Of the remaining studies, 73 publications met the inclusion criteria and were further investigated in detail. The search found 16 publications on anticonvulsants [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], 20 on atypical antipsychotics [ 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], 2 on lithium [ 49 , 50 ], 28 on antidepressants [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations